What is energy poverty? A concept analysis - Zainudin, Norzalina; Mohamad, Ummu Khalilah; Osman, Syuhaily; Lau, Jasmine Leby (Human Resources Management Academic Research Society (HRMARS), 2023)
Defining concept of energy poverty plays crucial in problem-solving such as policy design. This paper discusses conceptual definition of energy poverty which provides a rich vocabulary representing functions together with clear definitions grounded from literature. This study synthesizes the concepts of energy poverty from 2012 to 2022 in two major databases which is Web of Science (WOS) and Scopus. There are 45 eligible articles were counted in this review. The variation in the concept of energy poverty reveals its dimensionality. Energy poverty can be considered as lack of income and monetary aspects, lack of basic needs and material assets, lack of capability and energy inefficient. However, when closely examined, these dimensions are seen to be conceptually interrelated and complementary rather than substitutable. The concept used to define energy poverty determined the methods employed to measure it. The definition of energy poverty provided in this concept analysis will facilitate proper interpretation of the meaning of energy poverty and standardization of tools used to measure and monitor energy poverty. Energy poverty eradication purports to positively affect the economic growth of nations and hence improve the well-being of households.